2013
DOI: 10.1111/dmcn.12263
|View full text |Cite
|
Sign up to set email alerts
|

The role of serotonin receptor alleles and environmental stressors in the development of post‐concussive symptoms after pediatric mild traumatic brain injury

Abstract: Aim To determine whether post‐injury depressive symptoms, and pre‐injury major life stressors and genetic factors (HTR1A C(‐1019)G alleles; rs6295) are more common in children with mild traumatic brain injury (mTBI) who develop postconcussion syndrome (PCS) symptoms compared with children with asymptomatic mTBI. Method This was a cross‐sectional study of 47 symptomatic children (32 males, 15 females; mean age 14y [SD 3y 3mo]) who experienced post‐concussive symptoms for 7 or more days and 42 asymptomatic child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…In their cross-sectional study of 47 symptomatic children who experienced postconcussive symptoms for 7 or more days, the G allelic frequency and genotypic frequency for HTR1A polymorphisms was similar to that among controls. 64 In another study, S100B, an astroglial calcium-channel binding protein was found to be elevated after mild to severe TBI. 1 S100B is also highly correlated with abnormal cranial CT scans of mTBI patients; sensitivity is remarkable (90%-100%).…”
Section: Future Directionsmentioning
confidence: 94%
See 1 more Smart Citation
“…In their cross-sectional study of 47 symptomatic children who experienced postconcussive symptoms for 7 or more days, the G allelic frequency and genotypic frequency for HTR1A polymorphisms was similar to that among controls. 64 In another study, S100B, an astroglial calcium-channel binding protein was found to be elevated after mild to severe TBI. 1 S100B is also highly correlated with abnormal cranial CT scans of mTBI patients; sensitivity is remarkable (90%-100%).…”
Section: Future Directionsmentioning
confidence: 94%
“…18,48 As a result, many have recently focused efforts on identifying biomarkers that might predict or be hallmarks of PCS development. Noting that the G(-1019) allele of HTR1A is associated with major depression and suicide, a team led by Smyth et al 64 examined the prevalence of the G(-1019) allele in children with mTBI. In their cross-sectional study of 47 symptomatic children who experienced postconcussive symptoms for 7 or more days, the G allelic frequency and genotypic frequency for HTR1A polymorphisms was similar to that among controls.…”
Section: Future Directionsmentioning
confidence: 99%
“…Those that have been completed investigated the APOE e4 allele and serotonin receptor alleles, with inconsistent results. [13][14][15] Genome-wide investigations have demonstrated that the genetic predisposition to complex traits is highly polygenic (i.e., many variants with small effects). 16 Risk alleles identified by genome-wide association studies (GWAS) can be investigated in cross-phenotype investigations.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of alterations in limbic-frontal circuitry after concussion that resembles the functional alterations seen in major depression (Chen et al, 2008). Other neurochemical changes consistent between mood disorders and concussion are the presence of serotonin disturbance (Smyth et al, 2014) and decreased dopamine in the prefrontal cortex and brainstem (Chen et al, 2008; Sheline, Wang, Gado, Csernansky, & Vannier, 1996; Venzala, Garcia-Garcia, Elizalde, & Tordera, 2013). Organic brain changes may provide an explanation for mood and anxiety symptoms post-injury in the absence of pre-injury mental health conditions.…”
Section: Anxiety and Mood Clinical Profilementioning
confidence: 99%